"that headquarters of fanaticism and disaffection": Protest and the construction of space at Parihaka in the 1880s - Schmidt, Tyson (Architectural History Aotearoa, 2021)
At the 2009 version of this symposium I presented a paper that outlined how protests at Waitangi during the 1980s were played out architecturally through the media. Despite the heavy focus on biculturalism during the 1980s, reporting of proceedings at Waitangi on February 6th each year clearly showed a trifurcation of space. Television networks and the national newspapers showed that the "landscape of nationhood" was in fact inhabited by three actors in the symbolically important rituals - the State, tame Māori, and wild Māori. This trifurcation of space also played out a hundred years earlier at Parihaka. Sue Abel’s examinations of media constructions of nationhood and cultural interaction can be identified in reports on happenings at Parihaka pā through the 1880s. From the passive resistance to the Crown’s persistent surveying of the land and building of roads, the frequent large hui held at Parihaka that drew Māori from around the country, through to the invasion of the pā by a government force of more than 1500 troops – there was rich material for spatial representation by the media of the time. While the channels were different (dominated by newspapers and Parliamentary reports, with no television networks), this paper shows that the message of trifurcation was as strong in the 1880s as it would be in the 1980s.